2016
DOI: 10.7844/kirr.2016.25.5.14
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Research and Technical Development of Sorbents for Hot Gas Desulfurization for H2S Removal

Abstract: Theoretical reviews of integrated gasification combined cycle one of the clean coal technologies and trends in the study and technology development for high temperature desulfurization sorbents were investigated. Reactivity, durability and abrasion resistance is an important key for development of high temperature desulfurization sorbents, the kind of things include calcium, zinc, manganese, iron and copper-based sorbents. Current status of high temperature desulfurization sorbents, manufacturing techniques of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In addition, the reason for SO 2 generation is still unknown [18][19][20]. There are some studies reporting that the formation of SO 2 is due to the reaction between the side products (ZnSO 4 ) of the desulfurization and H 2 O [21][22][23][24][25][26][27]. Park et al [25,26] also observed SO 2 during desulfurization over the reaction between the reducing gases (CO and H 2 ) and ZnSO 4 , which was produced during the regeneration of sorbent under conditions of a low regeneration temperature and an excessive O 2 injection.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the reason for SO 2 generation is still unknown [18][19][20]. There are some studies reporting that the formation of SO 2 is due to the reaction between the side products (ZnSO 4 ) of the desulfurization and H 2 O [21][22][23][24][25][26][27]. Park et al [25,26] also observed SO 2 during desulfurization over the reaction between the reducing gases (CO and H 2 ) and ZnSO 4 , which was produced during the regeneration of sorbent under conditions of a low regeneration temperature and an excessive O 2 injection.…”
Section: Introductionmentioning
confidence: 99%